PENINGKATAN KOMPETENSI GURU MATEMATIKA SMP DALAM MERANCANG PERANGKAT PEMBELAJARAN ETNOSAINS DI KECAMATAN SALAHUTU - Pieter Z. Tupamahu; Christi Matitaputty; Widya Putri Ramadhani; Christina M. Laamena; Prelly M. J. Tuapattinaya (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to enhance the competence of junior high school Mathematics and Science teachers in Salahutu District, Central Maluku Regency, in designing ethnoscience-based learning materials. The main problems faced by the partner teachers were their limited understanding of the concept of ethnoscience and the lack of references and concrete examples of learning materials based on local wisdom. The program was implemented through a participatory and collaborative approach involving 24 teachers from five junior high schools. It consisted of five stages: preparation and coordination, training implementation, evaluation, implementation and trial of the learning materials, and sustainability strengthening. Data were collected through pre- and post-training questionnaires, observation sheets, student feedback instruments, and documentation. The data were then analyzed using quantitative and qualitative descriptive methods. The results of the pre-training questionnaire showed an average score of 82.17% in the very good category, with the lowest score found in the aspect of reference availability at 68.75%. After the training, all participants gave positive responses regarding the usefulness and clarity of the materials, as well as the assistance provided in developing learning materials. A total of 24 teachers successfully produced Teaching Modules, Student Worksheets, and student feedback instruments based on local contexts, namely the sale of rujak at Natsepa Beach, coconuts at the ferry port, and boiled corn, for the topic of Social Arithmetic. This program was effective in improving teachers’ understanding, skills, and motivation in developing contextual mathematics learning while simultaneously preserving the local culture of Maluku.